2017
DOI: 10.4236/jbbs.2017.712042
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of an Executive-Function and a Social Cognition Training on Preschoolers with Externalizing Behavior Problems

Abstract: In preschoolers, externalizing behavior problems are a primary cause of consultation. It is known that externalizing behavior (EB) could result from individual and environmental risk factors. Individual risk factors included notably social cognition (SC) and executive functions (EF). A high level of EB has usually been related to dysfunction in SC and to poor skills in EF. The aim of the present experimental study is to compare the impact of two very targeted child-oriented trainings in the increasing of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Several recent studies have shown the efficacy of training focusing on SIP for children of preschool and school age at risk of externalizing behavior. Such training improves social adjustment and decreases behavior problems Houssa, Volckaert, Nader-Grosbois, & Noël, 2017;Shure, 1993;Webster-Stratton & Hammond, 1997). Other studies have also reported positive effects of SIP training for children with autism spectrum disorders, with and without IDs (e.g.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several recent studies have shown the efficacy of training focusing on SIP for children of preschool and school age at risk of externalizing behavior. Such training improves social adjustment and decreases behavior problems Houssa, Volckaert, Nader-Grosbois, & Noël, 2017;Shure, 1993;Webster-Stratton & Hammond, 1997). Other studies have also reported positive effects of SIP training for children with autism spectrum disorders, with and without IDs (e.g.…”
Section: Introductionmentioning
confidence: 91%
“…A few SIP training programs have been developed for adolescents and adults with IDs (Anderson & Kazantzis, 2008;Cote, 2011;Crites & Dunn, 2004;Nestler & Goldbeck, 2011;O'Reilly et al, 2004;Vlachou & Stavroussi, 2016). Yet, most SIP programs have been implemented among children with externalizing behaviors at preschool and school age (for a review see Houssa, 2016;Houssa et al, 2016;Houssa et al, 2017); and some among children with autism spectrum disorder, with or without IDs (Bernard-Opitz et al, 2001;Radley et al, 2014). Such programs aim to help children to solve social problems, to distinguish benign or hostile intentions in critical social situations and to find the most appropriate behavioral response.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, manage his impulsivity could help in social problem solving. Houssa et al (2017) compared one program targeting inhibition ( Volckaert and Noël, 2015 ) and one focusing on social cognition ( Houssa and Nader-Grosbois, 2016 ). They showed that while the social cognition program increased social cognition skills, the inhibition intervention not only improved executive abilities such as inhibition, attention or working memory but also led to enhanced emotional regulation and social adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…‫ٝعٞك‬ ‫٣زٚؼ‬ ‫ٍجن‬ ‫ٝٓٔب‬ ‫ٝاُز٘ظ٤ْ‬ ‫اُز٘ل٤ن٣خ،‬ ‫اُٞظبئق‬ ‫ك٢‬ ً ‫ٍٔؼ٤ب‬ ‫أُؼبه٤ٖ‬ ‫ُلٟ‬ ‫ٝاٙؼ‬ ‫هٖٞه‬ ‫ٓضَ‬ ‫اُلهاٍبد‬ ٖٓ ‫اُؼل٣ل‬ ‫أًلرٚ‬ ‫ٓب‬ ‫ٝٛنا‬ ‫ا٫عزٔبػ٤خ‬ ‫ٝأُؼوك٤خ‬ ‫ا٫ٗلؼبُ٢،‬ (Horton & Silverstein, 2008;Hintermair, 2013;Morgan, 2015;Marschark et al, 2017;Hall et al, 2017;Gu et al, 2019 Henry et al, 2012;Figueras et al, 2008;Hintermair, 2013;Kronenberger et al, 2014;Hall et al, 2017). (Amadó et al, 2016;Gyurak et al, 2010;Houssa et al, 2017;Lantrip et al, 2016;Latronica, 2016;Lee et al, 2009;Penadés et al, Holley et al, 2017;Latronica, 2016;Marceau et al, 2018;Rueda & Paz-Alonzo, 2013;Soncin et al, 2016;Yang et al, The present study aimed to investigate the relationship between executive functions, emotional regulation and social cognitive among hearing-impaired children. In addition, study aimed at determining the effectiveness of a training program based on executive functions in improving the emotional regulation and social cognitive among the quasi-experimental sample.…”
mentioning
confidence: 99%